2017
DOI: 10.1111/een.12453
|View full text |Cite
|
Sign up to set email alerts
|

Plant and insect genetic variation mediate the impact of arbuscular mycorrhizal fungi on a natural plant–herbivore interaction

Abstract: Abstract. 1. While both arbuscular mycorrhizal (AM) fungi and plant and insect genotype are well known to influence plant and herbivore growth and performance, information is lacking on how these factors jointly influence the relationship between plants and their natural herbivores.2. The aim of the present study was to investigate how a natural community of arbuscular mycorrhizal fungi affects the growth of the perennial herb Plantago lanceolata L. (Plantaginaceae), as well as its interaction with the Glanvil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
(94 reference statements)
4
7
0
Order By: Relevance
“…Interestingly, bulbil sprouting was slower in the sterile soil than in the field soil, indicating that the soil microbial community stimulates sprouting. While this in part could be due to that sterilization affects nutrient levels, the observed effect agrees with previous studies, which found that soil organisms can advance phenology and influence plant growth (Wagner et al 2014, Rasmussen et al 2017, 2020). However, this study provided no insights into the putative adaptive nature of this pattern.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, bulbil sprouting was slower in the sterile soil than in the field soil, indicating that the soil microbial community stimulates sprouting. While this in part could be due to that sterilization affects nutrient levels, the observed effect agrees with previous studies, which found that soil organisms can advance phenology and influence plant growth (Wagner et al 2014, Rasmussen et al 2017, 2020). However, this study provided no insights into the putative adaptive nature of this pattern.…”
Section: Discussionsupporting
confidence: 91%
“…Every fortnight, starting 19 days after sowing, we recorded the number of leaves and the length and width of the longest leaf. From these measures, we calculated leaf size (leaf length × leaf width), total leaf area (leaf length × leaf width × number of leaves) and leaf allometry (leaf width/leaf length) (Rasmussen et al, ). We additionally measured plant rosette shape (flat or high) 74 days after sowing.…”
Section: Methodsmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi have received much attention and there appears to be a general pattern whereby generalist chewing insects are negatively affected by mycorrhizal presence, whilst specialist chewers and suckers are positively affected (Koricheva et al 2009). However, in many cases, there is a continuum of insect responses, from positive to negative, mediated by many factors including soil nutrient status, plant age, plant genetics, fungal identity, and extent of colonisation of the root system (Gange 2007;Rasmussen et al 2017;Tomczak and Müller 2017). One hitherto overlooked feature is whether the previous generation of plants had mycorrhizal associations and if they were attacked by the insect in question.…”
Section: Introductionmentioning
confidence: 99%